Vascular, valvular and kidney calcification manifested in mouse models of adenine-induced chronic kidney disease - Xin Yang; Yuqiu Liu; Xiaodong Zhu; Pingsheng Chen; Xiaotong Xie; Tian Xu; Xiaoliang Zhang; Yu Zhao (Renal Failure)
Background Ectopic calcification (EC) involves multiple organ systems in chronic kidney disease (CKD). Previous CKD-animal models primarily focused on a certain histological abnormality but did not show the correlation with calcified development among various tissues. This study compared calcified deposition in various tissues during CKD progression in mice.Methods Male 8-week-old C57BL/6J mice were randomly allocated to the seven groups: a basic, adenine, high-phosphorus, or adenine and high-phosphorus diet for 12–16 weeks (Ctl16, A12, P16, or AP16, respectively); an adenine diet for 4–6 weeks; and a high-phosphorus or adenine and high-phosphorus diet for 10–12 weeks (A6 + P10, A4 + P12, or A4 + AP12, respectively).Results Compared to the Ctl16 mice, the P16 mice only displayed a slight abnormality in serum calcium and phosphorus; the A12 mice had the most serious kidney impairment; the A4 + P12 and A6 + P10 mice had similar conditions of CKD, mineral abnormalities, and mild calcification in the kidney and aortic valves; the A4 + AP12 and AP16 groups had severe kidney impairment, mineral abnormalities and calcification in the kidneys, aortic valves and aortas. Furthermore, calcium-phosphate particles were deposited not only in the tubulointerstitial compartment but in the glomerular and tubular basement membrane. The elemental composition of EC in various tissues matched the calcification of human cardiovascular tissue as determined by energy dispersive spectroscopy.Conclusions The severity of CKD was unparalleled with the progression of mineral metabolism disorder and EC. Calcification was closely related in different tissues and observed in the glomerular and tubular basement membranes.